2003
DOI: 10.1080/1025389031000146773
|View full text |Cite
|
Sign up to set email alerts
|

LY354740, an mGlu2/3 Receptor Agonist as a Novel Approach to Treat Anxiety/Stress

Abstract: Metabotropic glutamate (mGlu) receptors, which include mGlu1-8 receptors, are a heterogeneous family of G-protein coupled receptors (GPCRs) that function to modulate neuronal excitation and plasticity via pre-synaptic, post-synaptic and glial mechanisms. Agonists for group II mGlu receptors (mGlu2 and mGlu3), such as LY354740, have been shown to suppress enhanced glutamatergic excitations in brain synapses known to be involved in the expression of fear/anxiety in animals and humans. Systemic administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
145
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(157 citation statements)
references
References 48 publications
10
145
1
1
Order By: Relevance
“…c-Fos expression was induced by LY354740 in stress-related brain regions such as the amygdala, EW, and LC, and also in the thalamic and midbrain structures that process sensory information. It has been shown that systemically administered LY354740 reaches the brain at pharmacologically relevant concentrations (see Schoepp et al, 2003). However, we cannot rule out the possibility that , and LY354740-treated EPM-exposed (d) mice.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…c-Fos expression was induced by LY354740 in stress-related brain regions such as the amygdala, EW, and LC, and also in the thalamic and midbrain structures that process sensory information. It has been shown that systemically administered LY354740 reaches the brain at pharmacologically relevant concentrations (see Schoepp et al, 2003). However, we cannot rule out the possibility that , and LY354740-treated EPM-exposed (d) mice.…”
Section: Discussionmentioning
confidence: 89%
“…Based on animal and early human data, modulation of excitatory neurotransmission via mGlu2/3 receptors is a novel approach to treat anxiety, as well as other psychiatric disorders (Schoepp, 2001;Schoepp and Marek, 2002;Schoepp et al, 2003). (1S,2S,5R,6S)-2-aminobicyclo [3.1.0]hexane-2,6-dicarboxylic acid (LY354740) is a selective and potent agonist for mGlu2 and mGlu3 receptors (Monn et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations